Caring Behaviors of Student Nurses Following Clinical Experience Through Role Play and Traditional Method - F Rafii; F Oskouie; R. Mohammadi; A. Yarandi; F. Kabiri; H. Peyrovi; H. Haghani (Iran University of Medical Sciences, 2007)
Introduction and Aim: Caring is a multidimensional nursing concept that can be actualized within the baccalaureate nursing curriculum through the purposeful teaching and student-centered learning of core values. Teaching interpersonal issues is possible through various methods such as role-play. The current study was conducted with the aim of describing the caring behaviors of two groups of sophomore-level student nurses after implementing either role-play or traditional method as teaching method of choice.  Materials and Methods: The researchers used quasi-experimental study design using an equivalent control group and post-test. Fifty one nursing students were randomly assigned in either experimental or control group. After that members of the experimental group performed their clinical experience using role play and members of control group did practice as routine, caring behaviors of two groups were observed using CBI.  Results: In general, findings indicated that caring behaviors related to subscales "respectful difference to other" and "professional knowledge and skill" were, respectively, the most and the least frequent caring behaviors in both groups. Conclusion: More frequent occurrence of interpersonal aspects of caring in two groups indicates that in the beginning of professional nursing care, the sophomore-level students give priority to altruistic values. So, using approaches to develop and maintain interpersonal aspects of caring in nursing curriculum, coupled with changing the teaching methods of practical aspects of nursing care and appropriate integration of theory and practice is recommended.